Prevalence, Virulence Genes and Antimicrobial Resistance Profiles of Salmonella Serovars from Retail Beef in Selangor, Malaysia - Thung, Tze Y.; Radu, Son; Mahyudin, Nor A.; Rukayadi, Yaya; Zakaria, Zunita; Mazlan, Nurzafirah; Tan, Boon H.; Lee, Epeng; Yeoh, Soo L.; Chin, Yih Z.; Tan, Chia W.; Kuan, Chee H.; et al. (Frontiers in Microbiology, 2018)
The aim of the present study was to investigate the prevalence of Salmonella spp., Salmonella Enteritidis and Salmonella Typhimurium in retail beef from different retail markets of Selangor area, as well as, to assess their pathogenic potential and antimicrobial resistance. A total of 240 retail beef meat samples (chuck=60; rib=60; round=60; sirloin=60) were randomly collected. The multiplex polymerase chain reaction (mPCR) in combination with the most probable number (MPN) method was employed to detect Salmonella spp., S. Enteritidis and S. Typhimurium in the meat samples. The prevalence of Salmonella spp., S. Enteritidis and S. Typhimurium in 240 beef meat samples were 7.50%, 1.25% and 0.83%, respectively. The microbial loads of total Salmonella was found in the range of <3 to 15 MPN/g. Eight different serovars of Salmonella were identified among the twenty-three isolates, and S. Agona was the predominant serovar (26.09%). Interestingly, all the Salmonella isolates were resistant to penicillin, erythromycin and vancomycin, but the sensitivity was observed for tetracycline, gentamicin and amoxicillin/clavulanic acid. All 23 isolates were resistant to at least three antibiotics. Two S. Typhimurium isolates (8.70%) exhibited the highest multiple antibiotic resistance (MAR) index value of 0.56 which shown resistance to nine antibiotics. PCR analysis of virulence genes showed that all Salmonella isolates (100%) were positive for the invA gene. Meanwhile, pefA was only identified in S. Enteritidis and S. Typhimurium. The findings in this study indicate that retail beef products tested were widely contaminated with multi-drug resistant (MDR) Salmonella and various virulence genes are present among the isolated Salmonella serovars.